2022
DOI: 10.3389/fendo.2022.990667
|View full text |Cite
|
Sign up to set email alerts
|

Perirenalfat thickness is associated with bone turnover markers and bone mineral density in postmenopausal women with type 2 diabetes mellitus

Abstract: ObjectivesEmerging evidence demonstrated that perirenal fat may modulate bone metabolism through several pathological pathways. This study was aimed to assess the associations between perirenal fat thickness (PrFT) and bone turnover markers (BTMs) and bone mineral density (BMD) in postmenopausal women with type 2 diabetes mellitus (T2DM) and further explore the correlation between PrFT and osteoporosis.MethodsIn this cross-sectional study, a total of 626 participants with complete data were enrolled in this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Apolipoproteins may be risk factors for atherosclerosis and cardiovascular disease, according to earlier research (Frikke‐Schmidt, 2020; Mehta & Shapiro, 2022). A considerable link between apolipoproteins and the development of osteoporosis, however, has frequently been observed in recent years (Martineau et al., 2016; Wang et al., 2023). In this study, APOA1 and APOF were found to be significantly negatively associated with BMD, whereas APOL1 and APOD were significantly positively associated with BMD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apolipoproteins may be risk factors for atherosclerosis and cardiovascular disease, according to earlier research (Frikke‐Schmidt, 2020; Mehta & Shapiro, 2022). A considerable link between apolipoproteins and the development of osteoporosis, however, has frequently been observed in recent years (Martineau et al., 2016; Wang et al., 2023). In this study, APOA1 and APOF were found to be significantly negatively associated with BMD, whereas APOL1 and APOD were significantly positively associated with BMD.…”
Section: Discussionmentioning
confidence: 99%
“…The cross‐sectional study showed that APOA1 positively associated with osteocalcin (OC), L1‐L4 BMD, and T‐score in Chinese postmenopausal women. Additionally, it has been demonstrated that APOA1 is independently linked to a decreased risk of osteoporosis (Wang et al., 2023). The results showed that the risk of osteoporosis significantly decreased with the increase of APOA1.…”
Section: Discussionmentioning
confidence: 99%
“…Adiponectin also exhibits anti-osteoporotic activity, promoting differentiation and mineralization of osteoblasts and inhibiting the secretion of OPG [100]. Adiponectin stimulates the expression of osteocalcin, which acts as a hormone regulating glucose metabolism and fat mass [72,73,87,[101][102][103][104][105][106]. The potential effect of adiponectin on osteoblasts and osteoclasts, and therefore on bone remodeling, may be mediated through the endocrine system and may influence lipid metabolism.…”
Section: Adiponectinmentioning
confidence: 99%